Fingerprint wizards : the secrets of forensic science - Piper, Ross. (Mankato, Minn. : Capstone Press, 2008)
An introduction to forensic science procedures including the examination of fingerprints, DNA, gunpowder, fibers, and handwriting found at a crime scene.
Includes bibliographical references (p. 31) and index.
6.1
3-6
Keywords: Criminal investigation -- Juvenile literature; Fingerprints -- Identification -- Juvenile literature; Forensic sciences -- Juvenile literature; Criminal investigation; Fingerprints -- Identification; Forensic sciences; Criminal investigation; Fingerprints -- Identification; Forensic sciences